Antioxidant Potential in Atopic Dermatitis: A Systematic Review - Zhou, Suyong; Jinfang Zhang (Scientific Journal of Dermatology and Venereology, 2023)
Introduction: Various antioxidants have been investigated for their potential role in managing atopic dermatitis. These include vitamins such as vitamins E and C, minerals like selenium, plant-derived polyphenols like green tea and resveratrol, and natural compounds like curcumin. These antioxidants possess diverse mechanisms of action, ranging from scavenging free radicals to modulating inflammatory pathways, and have shown promising results in preclinical and clinical studies. This study aimed to conduct a systematic study of the antioxidant potential in atopic dermatitis. Methods: The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the potential of antioxidants in atopic dermatitis. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Results: Antioxidant compounds such as vitamin E, vitamin C and flavonoids in each of the studies showed potential clinical improvement in atopic dermatitis patients. Conclusion: Antioxidant compounds have potential as supplementation for the management of atopic dermatitis.